Syilling Fantastic Enterprise : Smart Laundry / Aswad Abadh Dhar Nor Azman...[et al.] - Nor Azman, Aswad Abadh Dhar; Abd Hamid, Muhammad Faez; Baharuddin, Khairullah; Hasan, Mohd Hazwan (2019)
Syilling fantastic Enterprise, is the new company that wanted to promote a new product that can be marketed to the whole world. Actually our product name is “Electrical Laundry”. This smart laundry is the laundry that has been develop into something new product that can make all people woks getting easier. This product has been designed by our designer. Our product theme is ‘classic’. Syilling Fantastic Enterprise is come from our director’s idea. The word ‘syilling’ meaning that each paper money in this world was not enough if there were no ‘syiling’ to complete it. Besides, the words “fantastic” meaning that we praise our company so that the whole world will now our company name. This is a little bit of our company history.